Acute Toxicity, Antipyretic and Antinociceptive Study of the Crude Saponin from an Edible Vegetable: Vernonia Amygdalina Leaf - Adiukwu, Paul Chukwuemeka; Agaba, Amon; Nambatya, Grace; Adzu, Bulus; Imanirampa, Lawrence; Twinomujuni, Silvano; Twikirize, Osbert; Amanya, Martin; Ezeonwumelu, Joseph Obiezuchukwujekwu; Oloro, Joseph; Okoruwa, Godwin Aiyabalu; Katusiime, Barbra (International Journal of Biological and Chemical Sciences, 2012)
Vernonia amygdalina is commonly used for food and health purposes. Processing of the leaf for food is aimed at removing bitter tasting antinutritional principles like saponins. This study was designed to determine the antipyretic and antinociceptive property of the crude saponin from Vernonia amygdalina leaf. Standard procedure for antipyretic study using Saccharomyces cerevisiae induced pyrexia in rats; and acetic acid induced writhe, hot plate and cold tail flick tests for antinociceptive study in mice were used. Data for the crude saponin showed significant (P ≤ 0.05) dose dependent anal temperature decrease. The antinociceptive data in mice was significant (P ≤ 0.05) in the writhing test contrary to the cold tail flick test. In acute toxicity study, an LD50 of 5.1523 g/kg using oral route indicated it was practically non-toxic. Finding suggests that Vernonia amygdalina leaf prepared as diet could be of potential benefit to ailing persons with fever and/or pains, if processing technique adopts minimal loss of principles like saponins.
Keywords: Mice, oral, pain, pyrexia, rat